Annual Report on Exchange Arrangements and Exchange Restrictions 2015. (Annual Report on Exchange Arrangements and Exchange Restrictions, 2015)
This is the 66th issue of the AREAER, which provides comprehensive descriptions of the foreign exchange arrangements, exchange and trade systems, and capital controls of all IMF member countries. It describes each country's market operations, international trade policies, controls on capital transactions, and financial sector measures. AREAERs from 1988 are available on IMF eLibrary, and cumulative data from each annual report dating back to 1999 are available in a single online database, AREAER Online (see below). The 2015 AREAER includes a print version of the Overview and key summary tables and a CD that includes 191 individual country chapters.